Financial crises and information transfer: An empirical analysis of the lead-lag relationship between equity and CDS iTraxx Indices - Stefan Ehlers; Marc Gürtler; Sven Olboeter (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2010)
This study examines the lead-lag-relationship between European equity and CDS markets in the context of the financial crisis. Previous research identified the stock market to lead the CDS market in an ordinary economic environment. Against the background of our study this lead-lag-relationship strengthens when moving from the non-crisis- to the crisisscenario on a daily as well as on a weekly basis. Hence, we conclude that information transfer from stock to CDS markets widens during the financial crisis. In addition and in contrast to the literature we find an extraordinary day-of-the-week-effect on weekly returns as an anomaly for information processing.
Keywords: G14; G15; G17; 330; Granger-causality; iTraxx Indices; Credit Default Swaps; Day-of-the-Week-Effect; Feedback System